2019
DOI: 10.18203/2394-6040.ijcmph20190222
|View full text |Cite
|
Sign up to set email alerts
|

A study on breast feeding practices among mothers in urban field practice area of tertiary care center, Hyderabad

Abstract: Background: Breastfeeding is the best preventive intervention and has potential impact on child mortality. Breastmilk is safest, least allergic and has nutritional, immunological, behavioural and economic benefits. It also provides desirable mother baby bonding. Early human milk promotes gut maturation and immune activation in infants. Despite of the demonstrated benefit of breastfeeding, the duration and prevalence are still low in first six months of life. The objectives of the study were to estimate the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Other studies have reported a higher percentage of mothers giving pre-lacteal feeds. [15][16][17] Burping the baby after feed which is an important measure to prevent GI disturbances such as colic and aspiration in newborn was lacking. In the current study burping after the feed was done by 88% mothers from urban area, whereas nearly half the mothers from rural area did not carry out burping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported a higher percentage of mothers giving pre-lacteal feeds. [15][16][17] Burping the baby after feed which is an important measure to prevent GI disturbances such as colic and aspiration in newborn was lacking. In the current study burping after the feed was done by 88% mothers from urban area, whereas nearly half the mothers from rural area did not carry out burping.…”
Section: Discussionmentioning
confidence: 99%
“…Cheedarla et al reported practice of burping after the breastfeeding was followed by 71% urban mothers. 16 The assessment of the practice of burping has not been covered by many studies.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in a study done by Gopalakrishnan et al [18] The prevalence was found to be comparatively lower in studies conducted by Chedarla et al (64%) and Umadevi et al (38.8%). [1920] This may be attributed to the increased awareness of the study population on the benefits of exclusive breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, the World Health Assembly has set a global nutrition target, that in 2025 at least 50% of infants should be exclusively breastfeeding at six months of age. 9 Developed countries keep on witnessing low breastfeeding rates. Globally, only 38% of infants are exclusively breastfed at six months of age.…”
Section: Introductionmentioning
confidence: 99%